Penerapan metode problem solving dalam meningkatkan kemampuan literasi membaca teks persuasi pada peserta didik kelas VIII A SMP Negeri 15 Palu - Wiana, Wiana; Nuraeni, Ida (Universitas Mulawarman, 2024)
This study aims to describe the application of problem-solving methods to improve the reading literacy skills of persuasive texts in class VIII A students of SMP Negeri 15 Palu. This research is classroom action research using two cycles. Data collection techniques were observation and giving learning outcome tests at the end of each cycle. The data analysis technique was qualitative. The results showed that in cycle I, the aspect of identifying was 71, the aspect of completeness of structure was 73, and the aspect of linguistic rules was 74. From all aspects assessed, classical learning completeness was obtained at 60%, the results of teacher activity observation were 67.39%, and the results of student activity observation were 62.5%. In cycle II, there was a significant increase, especially in identifying which was worth 93, the completeness of the structure was worth 77, and the linguistic rules aspect was worth 82. Classical learning completeness in cycle II reached 92%, teacher activity observation results were 96.73%, and student activity observation results were 97.5%. It shows that applying the problem-solving method can improve the literacy skills of reading persuasive texts in class VIII A students of SMP Negeri 15 Palu.